NATIONAL CANCER INSTITUTE STANDARDS FOR COMPREHENSIVE SMOKING PREVENTION AND CONTROL (Tufts Archival Research Center, 2007)
Strategy put forth by the National Cancer Institute to reduce cancer mortality rates by 50%. Provides a comprehensive framework for achieving these goals. Lists the various tactics believed to be effective in achieving this goal such as identifying target groups in order to tailor anti-smoking efforts to be more successful.